2018
DOI: 10.1093/femsec/fiy083
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic community successions and interactions in marine biofilms: the key role of Flavobacteriia

Abstract: Despite clear advances in characterizing marine biofilms, details on their formation and species succession remain scarce particularly during the early stage of development. We investigated the microbial community composition and succession in coastal marine biofilms on plastic. Samples were collected over 75 days of immersion with strengthened samplings during the early stages of biofilm establishment. Biofilm composition was estimated using Illumina Miseq and microbial community interactions were assessed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
113
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 84 publications
9
113
0
1
Order By: Relevance
“…On day 3, corresponding with the average startup time of EDC+WW reactors, the only OTU that became differentially abundant in EDC+WW relative to the control planktonic communities belonged to Sphingobacteriia . This finding is consistent with the functional role attributed to Flavobacteriia and Sphingobacteriia , both of which were found to represent key members in the formation and functioning of biofilms in diverse environments (Battin et al, 2016; Nagaraj et al, 2017; Pollet et al, 2018), probably due to their ability to degrade diverse complex organic material and their superior attachment ability. Furthermore, Sphingobacteriia were previously reported in bioelectrochemical devices both at the plankton fraction and anodic biofilm as homoacetogens or fermenters of complex organic substances that support electrogenic species within the biofilm through syntrophic interactions (Gao et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…On day 3, corresponding with the average startup time of EDC+WW reactors, the only OTU that became differentially abundant in EDC+WW relative to the control planktonic communities belonged to Sphingobacteriia . This finding is consistent with the functional role attributed to Flavobacteriia and Sphingobacteriia , both of which were found to represent key members in the formation and functioning of biofilms in diverse environments (Battin et al, 2016; Nagaraj et al, 2017; Pollet et al, 2018), probably due to their ability to degrade diverse complex organic material and their superior attachment ability. Furthermore, Sphingobacteriia were previously reported in bioelectrochemical devices both at the plankton fraction and anodic biofilm as homoacetogens or fermenters of complex organic substances that support electrogenic species within the biofilm through syntrophic interactions (Gao et al, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…At the class level, we found that all inshore biofilms collected were predominantly composed of Alphaproteobacteria , Gammaproteobacteria , although they also all harboured Flavobacteriia , Sphingobacteria, Bacteroidetes , Cytophagia, Deltaproteobacteria and Verrumicrobiae at different relative abundances. The previous studies of biofilms have similarly found that Alphaproteobacteria , Gammaproteobacteria and Bacteroidetes (comprised mainly of Flavobacteria , Sphingobacteria and Cytophagia ) dominate in young coastal marine biofilms and also in freshwater stream biofilms (Elifantz et al ., ; Battin, ; Pollet et al ., ). Rhodobacteraceae species are also generally found as primary colonizers in costal marine biofilms (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Rhodobacteraceae species are also generally found as primary colonizers in costal marine biofilms (e.g. Dang et al ., ; Elifantz et al ., ; Pollet et al ., ) and are ubiquitous and abundant microbial components in diverse marine samples (Buchan et al ., ). Our results are in agreement with other studies of environmental marine biofilms where at higher taxonomical levels (phyla and class) similar taxa were reported, suggesting that they may represent primary biofilms colonizers, while they are generally distinctive at the species level (Elifantz et al ., ; Battin, ; Pollet et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…) exhibited both OTUs and metabolites which were more abundant in the spring and positively correlated to each other. Most of the corresponding taxa were related to Alteromonadaceae, especially members of the BD1‐7 clade which have been previously reported as pioneer bacteria on marine surfaces (Dang and Lovell, ; Pollet et al ., ) and in nutrient‐depleted environments (Spring et al ., ). If already identified in the low nutrients containing Mediterranean Sea, the BD1‐7 clade was not reported as a major taxon of biofilms formed on artificial substrates in the vicinity of the collection site (Briand et al ., ), indicating a potential specific selection by T. atomaria .…”
Section: Discussionmentioning
confidence: 99%